Effect of low dose aspirin application during pregnancy on fetal congenital anomalies - Si Sun; HongYang Qian; Congcong Li; Qiaohong Wang; Aimin Zhao (BMC Pregnancy and Childbirth, 2022)
Abstract Background With the extensive use of aspirin in obstetrics and reproductive medicine, concerns of potentially related congenital anomalies have been raised in previous studies. However, there is a lack of evidence concerning the safety of application of aspirin during pregnancy in Chinese population, especially during the first trimester. Patients and methods We retrospectively included a total of 2,763 patients with 2,856 fetuses (2670 singleton births and 93 pairs of twins), among whom 1,684 took low dose aspirin (LDA) during pregnancy (the LDA group) and the other 1,079 were not exposed to LDA (the control group). The primary outcome was the rate of fetal congenital anomalies, and was compared between the LDA group and the control group. We also conducted logistic regression to examine the potential risk factors of congenital abnormalities. Results The average daily dose of LDA taken was 67.6 mg. The rate of congenital anomalies was comparable between the two groups, suggesting low teratogenicity of LDA application during pregnancy (3.3% vs. 2.8%; P = 0.421). The duration of LDA exposure and the time of LDA exposure showed no association with congenital anomalies. A previous history of fetal congenital anomalies was associated with an increased risk of the recurrence of congenital anomalies in the siblings (adjusted OR = 3.00, 95% CI: 1.00–8.60; P = 0.041). Conclusion Exposure to LDA during pregnancy did not increase the risk of congenital anomalies in the fetus, suggesting that it was safe to apply LDA during pregnancy. A history of previous fetal abnormalities was found to be an independent risk factor of congenital anomalies. Our study suggests that LDA can be safely applied during pregnancy without increasing risks of congenital anomalies.